GABARAP ameliorates IL-1β-induced inflammatory responses and osteogenic differentiation in bone marrow-derived stromal cells by activating autophagy - Xiaobo Guo (Nature Portfolio, 2021)
Abstract Bone mesenchymal stem cells (BMSCs) are the most commonly investigated progenitor cells in bone defect repair and osteoarthritis subchondral bone regeneration; however, these studies are limited by complex inflammatory conditions. In this study, we investigated whether pro-autophagic γ-aminobutyric acid receptor-associated protein (GABARAP) promotes BMSCs proliferation and osteogenic differentiation by modulating autophagy in the presence or absence of interleukin-1 beta (IL-1β) in vitro. The expression levels of all relevant factors were evaluated by qRT-PCR or western blotting where appropriate. BMSCs differentiation were assessed by Alizarin Red, alkaline phosphatase, safranin O, and Oil Red O staining. Furthermore, the interactions between autophagy and osteogenic differentiation were investigated by co-treatment with the autophagy inhibitor 3-methyladenine (3-MA). As the results, we found that treatment with recombinant human His6-GABARAP protein promoted cell proliferation, inhibited apoptosis, and reduced ROS generation by increasing autophagic activity, particularly when co-cultured with IL-1β. Moreover, His6-GABARAP could effectively increase the osteogenic differentiation of BMSCs. The expression levels of inflammatory factors were significantly decreased by His6-GABARAP treatment, whereas its protective effects were attenuated by 3-MA. This study demonstrates that GABARAP maintains BMSCs survival and strengthens their osteogenic differentiation in an inflammatory environment by upregulating mediators of the autophagy pathway.